Prioridades de gestión de tecnologías de información en organizaciones peruanas - Santana Ormeño, Martín (2016)
It is interesting to observe how technological development has allowed to several organizations to use information technologies as tools, not only for improvements in operational efficiency, but also as support to achieve innovation and creating new opportunities. The aim of the study is to understand the priorities of information technologies management in Peruvian organizations. The study is considered a cross-sectional investigation with repeated measurements of 119 and 150 executives in the years 2010 and 2011 respectively. The sample was not random and a questionnaire to all participants applied online. The results evidence that the processes management, business agility and strategic alignment represent the most important management priorities and the budget assigned to technology areas maintains an upward trend despite the impacts of the international crisis on the Peruvian economy. These findings may help managers understand the value of information technologies for businesses to make better investment decisions on technology.